Poznawanie siebie i poznawanie innego. Wobec inności literatury - Łebkowska, Anna (Przestrzenie Teorii, 2007)
In my paper, I deal with the relationships between the present-day discourse in literature and literature itself: mainly in the aspect of the category of "otherness." Among many current understandings of that category, I analyse those for which literature is the sphere of what is distinct. That prospect also allows me to identify the experience of "otherness," being initiated owing to literature, and that only in the manner available to literature. The category of "other-ness" is associated with the same meanings in which it appears in both present-day literature and cultural anthropology, consequently, it is identified with ethnic and gender distinctness, or the area of exclusion, or, just the opposite, the area of inclusion contrary to one's w ill, or alienation etc. In my paper, I concentrate on the methods of literary thematicality of learning about oneself and "the other" (I mainly lim it myself to personal relationships, or novelistic " I" - "the other" relationships), which are present at various levels of present-day prose. I also take into account those literary strategies which serve the destabilization of both social and literary conventions and demonstrate "the otherness in the otherness" of literature. In conclusion, I point out dangerous trends which appear in literary studies: the one which leads either to excessive ideologization of literature or, vice versa, to excessive unification of the varieties of "otherness" presented in literature.